Petrography of Jutana Dolomite: Implications for Geotechnical Utility: Petrography of Jutana Dolomite: Implications for Geotechnical Utility - Mustafa Yar; Umer Jabbar Khan; Mian Gulzeb Joya; Muhammad Saqib Javed (International Journal of Economic and Environmental Geology, 2017)
Present study has been carried out to know the reliance of mechanical properties on the petrographic parameters. The Jutana dolomite is comprised of dolomite, sandy dolomite and siliciclastic beds. In this study microfacies analysis and geotechnical utility of Jutana dolomite has been determined. Based on the microscopic study different microfacies were identified. The mechanical properties of Jutana dolomite were investigated with the help of the strength tests such as uniaxial compressive strength (UCS) and uniaxial tensile strength (UTS) and shear strength. The results of the strength tests show that the Jutana dolomite is a moderately strong, which is suitable for construction purpose. In addition, the interrelationships of petrographic and mechanical properties of Jutana dolomite were determined. The percent quartz (8-41%) grains play a positive impact on the uniaxial compressive strength of Jutana dolomite. Key words: Petrography, dolomite, uniaxial compressive strength, Khewra gorge.